Thyroid Hormones in Sediment and Water: Method Validation and Detection in Taihu Lake of China - Zhang, Shuzhan; Zhang, Jiaxin; Chang, Hong; Sun, Fuhong (Frontiers in Environmental Science, 2021)
Study of the occurrence and fate of thyroid hormones in aquatic environments requires a highly sensitive method that is capable of detecting such compounds at sub-ng/L concentrations. By using isotope-dilution UPLC-MS/MS, we developed a sensitive method for quantifying thyroxine (T4), 3,3ʹ,5-triiodothyronine (T3), 3,3ʹ,5ʹ-triiodothyronine (rT3), iodotyrosine (MIT), and 3,5-diiodotyrosine (DIT) in lake water and sediment samples. MIT and DIT were first reported in aquatic environments in this study and were detected in all sediment and water samples with concentrations of 0.01–1.1 ng/g dw and 1.9–9.9 ng/L, respectively. T4 was only observed in sediment, with the measured concentrations and frequency of <LOQ-0.07 ng/L and 87%, respectively. T3 and rT3 were not found in this study. It was observed that the MIT/DIT ratios in sediment (2.4 ± 0.92) were significantly higher than those in water (0.84 ± 0.18), and the MIT/DIT ratios significantly correlated with DOC values in water samples, indicating that sorption to organic C could be of important mechanism. In addition, aquaculture, livestock and poultry farms probably were the important sources for the pollution of MIT, DIT, and T4 in Taihu Lake.